PREDICTION OF CRITERIA VARIABLE SOCIAL DANCES RESULT ON MORPHOLOGICAL CHARACTERISTIC BASIS - Amra Nožinović Mujanović; Zumreta Nožinović; Lejla Salihamidžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In this research we had the sample of male students, from Faculty of physical education and sport in Tuzla, age of 20 to 22 years old. The number of whole sample was 156. Mesuring is being done by using 20 tests of morphological characteristics and 4 Social. Regression analysis was used in the aim of establishment the influence largness of preliminary mentioned prediction set on criteria variable. With regression analysis of Social dances in manifested space of morphological variables, we got enough information about used variables influence on success of performing treated criteria variable, respectively, the coefficients of multiplecorrelation are high. Those kinds of research are pretty unusually, so we suppose this could be a small contribution to make a better training quality, by Social dances as also by other dance distributions.